Evaluation of the efficiency of the diversification mechanism gas supply to ukraine in the reverse direction (Economics and region, 2020)
The priority national interests in the field of energy, which determine the strategic objectives of ensuring energy security, are the reliable provision of energy resources for the needs of the national economy and increase the level of energy independence of the national economy and ensure the proper participation of Ukraine in the implementation of international energy projects. Diversification of sources and routes reduces political, technological and security risks of gas supply. This article presents a predictable estimate of the possibilities of gas supply in reverse direction through existing gas transportation systems. It is provided for discussion in the expert environment forecasts of gas supplies through existing gas transportation systems, by calculating the minimum possible volume of transit natural gas to ensure the profitability of its transportation, which allows to assess the real possibilities of reverse gas supplies to Ukraine.
Keywords: evaluation; mechanism efficiency; reverse gas supply; contract; natural gas transportation; energy independence; economy